Development and psychometric validation of the hospitalized patients’ expectations for treatment scale-clinician version - Dai, Bindong; Xiao, Chunfeng; Wang, Yufei; Li, Tao; Duan, Yanping; Jiang, Yinan; Shi, Lili; Hong, Xia; Geng, Wenqi; Hu, Jiaojiao; Cao, Jinya; Wei, Jing (Frontiers in Psychiatry, 2024)
Objective: Patient safety management systems in general hospitals require a comprehensive tool for assessing the expectations of inpatients across different wards. This study aimed to develop and psychometrically validate a new scale, the Hospitalized Patients' Expectations for Treatment Scale-Clinician version (HOPE-C), to meet this requirement.We interviewed 35 experts and 10 inpatients while developing the HOPE-C scale. The scale was initially designed with three dimensions: clinicians' expectations regarding doctor-patient communication, clinicians' expectations regarding treatment outcome, and clinicians' expectations regarding disease management. We recruited 200 inpatients from a general hospital in China. At the same time, 51 clinicians were assigned to the enrolled patients who completed the HOPE-C to examine the reliability, validity, and psychometric characteristics of the questionnaire. We applied item analysis, assessed construct validity, evaluated internal consistency, and conducted a test-retest reliability analysis over 7 days.Results: Both exploratory and confirmatory analyses supported a 2-dimensional structure, comprising doctor-patient communication expectations and treatment outcome expectations, with 批注 [A1]: The manuscript has been formatted as per the following link: https://www.frontiersin.org/guidelines/author-guidelines and the suggested template has been used.